The Sarajevo Ghetto Spectacle: An Introduction to the History of the Visual Arts Scene of Besieged Sarajevo. Issue 3 (3rd May 2020) - Kumelowski, Ewa Anna
Abstract: This article aims to provide the first comprehensive overview of the activities of the visual arts community active during the siege of Sarajevo (1992–1995), focusing on the shifts in practical and discursive artistic practice as well as on developments in curatorial practice. While most studies have focused on individual instances of cultural production, this article proposes a more extensive analysis of the visual arts as a whole, building a foundation for a study of changes in civilian life in response to the siege through the prism of the work of artists. This allows for the exploration of how everyday dangers of prolonged conflict heavily impacted the local art scene, encouraging the use of new materials and discursive framing based on the realities of war, and ushered in new and radical ways of integrating a traditional artistic community with the broader urban public.